Screening and identification and fermentation conditions optimization of high yield ethyl acetate yeast - LI Qiuxiao, PANG Zemin, ZHANG Ru, CHEN Xi, ZHAO He, DU Binghao, ZHU Lining, MA Huifeng, LI Xiuting, HAO Jianxiong (Zhongguo niangzao)
The yeast strains with high ethyl acetate production were isolated and screened from light-flavor (Qingxiangxing) Baijiu Daqu by traditional culture isolation method and ethyl acetate yield determination. The strain was identified by morphological observation and molecular biology, and its tolerance was analyzed. The fermentation conditions of the screened strains were optimized by single factor tests and response surface tests with ethyl acetate yield as the response value. The results showed that a yeast strain YM001 with high yield of ethyl acetate was isolated and screened, which was identified as Wickerhamomyces anomalus. The strain had strong tolerance and could still grow under the conditions of ethanol volume fraction 10%, acetic acid content 0.08%, temperature 50 ℃, pH 2, ethyl acetate content 30 g/L, NaCl content 150 g/L and glucose content 50 g/L, and could adapt to the Baijiu brewing environment well. The optimal fermentation conditions for W. anomalu YM001 to produce ethyl acetate were as follows: inoculum 4%, ethanol volume fraction 4%, acetic acid addition 0.02%, initial sugar content 9 °Bx, initial pH 6, rotation speed 210 r/min, fermentation temperature 22 ℃, the second stage fermentation time 36 h. Under these fermentation conditions, the yield of ethyl acetate produced by W. anomalu YM001 was the highest, reaching (17.39±0.362) g/L.